Diversity of aquatic and terrestrial molluscs from Simeulue Island, with notes on their distribution and some new records - Nova Mujiono; Heryanto Heryanto; Ristiyanti Marsetiyowati Marwoto (Biogenesis: Jurnal Ilmiah Biologi, 2020)
.